Integrating Local and Spiritual Values in Affective Assessment: Strategies of Islamic Religious Education Teachers - Rachmawaty, Silvia Siti; Anwar, Saepul; Abdillah, Hilman Taufiq (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
Affective assessment in Islamic Religious Education (IRE) plays a strategic role in shaping students’ character holistically and contextually. However, little is known about how IRE teachers integrate local and spiritual values into assessment practices at the junior high school level. This study uses a qualitative approach with an instrumental case study involving four IRE teachers at a public junior high school in Bandung. Data were collected through semi-structured interviews, classroom observations, and document analysis. Findings show that affective assessment was implemented through adaptive strategies grounded in local cultural values such as someah (hospitality and respect) and silih asih (mutual care and compassion). These practices were reinforced by reflective and collaborative approaches, revealing contextual and sustainable dimensions of affective assessment. This study contributes to the literature by demonstrating how local and spiritual values enrich affective assessment in IRE and offers a novel perspective on contextualized character education. Practical implications include the need for standardized affective assessment instruments, continuous professional development for teachers, and integration of affective assessment into curriculum policy as a transformative pedagogical tool.